PERLINDUNGAN HUKUM TERHADAP HAK RESTITUSI KORBAN PENIPUAN DAN ATAU PENGGELAPAN DI INDONESIA - Siska Ratnasari, (Proceeding International Conference on Social Sciences, 2026)
Article 7A paragraph (1) letter b of Law Number 31 of 2014 concerning Protection of Witnesses and Victims, that victims of criminal acts have the right to obtain restitution in the form of compensation for losses incurred due to suffering directly related to the consequences of the crime, but this has not been implemented in several jurisdictions of the Unitary State of the Republic of Indonesia for victims of fraud and/or embezzlement. Research objectives To analyze legal protection of the right to restitution for victims of fraud and/or embezzlement in Indonesia; To analyze inhibiting factors and efforts to overcome these obstacles. The research method is normative legal research with a statutory and case approach; data sources are secondary data consisting of primary, secondary and tertiary legal materials; data analysis is qualitative with inductive conclusions. The results of the research are First, legal protection of the right to restitution for victims of fraud and/or embezzlement in Indonesia has not been implemented properly where there are still perpetrators of criminal acts of fraud and/or embezzlement in Indonesia who do not provide restitution rights to their victims. Second, inhibiting factors and efforts to overcome obstacles in the legal protection of the right to restitution for victims of fraud and/or embezzlement in Indonesia. is the inability of the perpetrator to compensate the victim's material losses in restitution. The victim's efforts to receive any compensation for material losses from the perpetrator and the perpetrator is responsible for carrying it out; The procedure for submitting a restitution application is complicated and there are many requirements. The government's efforts to simplify regulations related to the procedures and requirements for submitting a restitution application; The perpetrator's low legal awareness where the perpetrator considers the court's decision regarding restitution to be a default on compensation arising from the crime that occurred and it is impossible for re-conviction to be carried out (Ne bis in idem). The panel of judges' efforts include in their decision that if restitution is not carried out, a replacement in the form of an additional prison sentence will apply to the perpetrator..